Caesarean section at maternal request – the differing views of patients and healthcare professionals: a questionnaire based study. (September 2015) - Sharpe, A.N.; Waring, G.J.; Rees, J.; McGarry, K.; Hinshaw, K.
Abstract: Objective: The number of caesarean sections at maternal request without medical indication is increasing. We aimed to explore the views of pregnant women, midwives and doctors using six hypothetical clinical scenarios and compare group views on: (a) perceived appropriateness of requests for caesarean section and (b) the reasons underlying these requests. Study design: A questionnaire was distributed to 166 pregnant women, 31 midwives and 52 doctors within maternity units at two hospitals in the North East region of England. Six hypothetical clinical scenarios for maternal requests were used: (1) uncomplicated first pregnancy, (2) one previous normal delivery, (3) one previous instrumental delivery, (4) one previous caesarean section, (5) one previous caesarean section with vaginal delivery since and (6) uncomplicated twin pregnancy. To highlight the differences in group responses, two main questions were asked for each scenario: 1. Should women be able to request a caesarean section? 2. What do you feel are the reasons for requesting a caesarean section? Data was analysed using Chi-squared or likelihood ratio as appropriate. Results: In scenarios 1–3, professional groups were ' less likely ' than pregnant women to always support a request (2.4% vs. 19.4%), (2.6% vs. 15.6%), (4.6% vs. 22%), ( p  < 0.001). No significant differences were shown between doctors and midwives except for scenario 6 (twins), where midwives more often felt maternal requests should be declined (26.1% vs. 1.9%) ( p  = 0.001). Multiparous women ( n  = 95) were more likely to agree 'sometimes' to maternal requests in scenarios 1, compared to nulliparous women ( n  = 71) (21.1% vs. 4.2%) ( p  = 0.04). ' Safety of the baby ' was ranked highly with pregnant women in scenarios 1–3 (mean 24.4%, range [15.8–38%]) compared with healthcare professionals (7.6% [3.4–12.8%]). However in scenario 3, healthcare professionals attributed ' fear of injury to self ' (29.6%) as the most likely reason compared to 14.6% of pregnant women. Conclusion: Healthcare professionals and pregnant women's views differ significantly. Multiparous patients' views differ from those who have not had children before. We should provide clearer information on risks and benefits which encompass areas that concern women most.